Effect of lactic fermentation on the antioxidant capacity of Malaysian herbal teas - Ibrahim, N. A.; Mustafa, Shuhaimi; Ismail, Amin (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
This study evaluated and compared the antioxidant capacity between freshly prepared and lactic fermented Malaysian herbal teas. Herbal teas are rich in antioxidants. Fermentation has been known to be the oldest and cost effective method with the ability to preserve or improve food nutritional qualities. Information on the antioxidant capacity of lactic fermented food or beverage is still lacking. Hence, the objective of this study is to determine the changes in the antioxidant properties of Malaysian herbal teas after being subjected to lactic fermentation. Commercially available local herbal teas were used for this study. Herbal teas such as “Allspice”, “Scaphium”, “Gora” and “Cinnamon” were purchased from the local store in Malaysia and were subjected to 24-hour lactic fermentation. Lactic fermented herbal teas were analyzed for their total phenolic, total flavonoid and antioxidant properties via DPPH, FRAP, and β-carotene linoleate bleaching assay. All lactic fermented herbal teas exhibited higher phenolic contents, flavonoid contents and antioxidant properties compared to the freshly-prepared herbal teas with majority showing significant changes (p < 0.05) in FRAP and β-carotene bleaching assay. Lactic fermented herbal teas also showed an increase in antioxidant capacity in DPPH assay, however non-significant changes were observed.